Methods of renal function assessment in arterial hypertension: the clinical value and practical implementation - Zh. D. Kobalava; Yu. V. Kotovskaya; S. V. Villewalde (Кардиоваскулярная терапия и профилактика, 2009)
This literature review is focused on the modern diagnostic methods in pre-clinical renal pathology. The wide prevalence of renal dysfunction in cardiovascular disease (CVD), its role in the stratification of cardiovascular and renal complication risk, and the potential for medical prevention of these complications justify the search for the methods diagnosing pre-clinical renal pathology. Increased serum creatinine, reduced creatinine clearance or estimated glomerular filtration rate (GFR), and microalbuminuria are independent predictors of cardiovascular morbidity and mortality. In all patients with arterial hypertension, estimated GFR and urinary albumin excretion should be assessed. Nephroprotective strategies, delaying progression of proteinuria and GFR reduction, should be identified.